Comparison of Two Central Venous Pressure Control Strategies to Prevent Atrial Fibrillation After Coronary Artery Bypass Grafting - Costa,Mario Augusto Cray da (2017)
Abstract Background: Atrial fibrillation (AF) takes place in 10-40% of patients undergoing coronary artery bypass grafting (CABG), and increases cardiovascular mortality. Enlargement of atrial chambers is associated with increased AF incidence, so patients with higher central venous pressure (CVP) are expected to have larger atrial distension, which increases AF incidence. Objective: To compare post-CABG AF incidence, following two CVP control strategies. Methods: Interventional, randomized, controlled clinical study. The sample comprised 140 patients undergoing CABG between 2011 and 2015. They were randomized into two groups, G15 and G20, with CVP maintained ≤ 15 cmH2O and ≤ 20 cmH2O, respectively. Results: 70 patients were included in each group. The AF incidence in G15 was 8.57%, and in G20, 22.86%, with absolute risk reduction of 14.28%, and number needed to treat (NNT) of 7 (p = 0.03). Mortality (G15 = 5.71%; G20 = 11.42%; p = 0.07), hospital length of stay (G15 = 7.14 days; G20 = 8.21 days; p = 0.36), number of grafts (median: G15 = 3, G2 = 2; p = 0.22) and cardiopulmonary bypass use (G15 = 67.10%; G20 = 55.70%; p = 0.22) were statistically similar. Age (p = 0.04) and hospital length of stay (p = 0.001) were significantly higher in patients who developed AF in both groups. Conclusion: Keeping CVP low in the first 72 post-CABG hours reduces the relative risk of AF, and may be useful to prevent AF after CABG.